Effect of Pregnancy on Interferon Gamma Release Assay and Tuberculin Skin Test Detection of Latent TB Infection Among HIV-Infected Women in a High Burden Setting. (1st May 2017) - LaCourse, Sylvia M.; Cranmer, Lisa M.; Matemo, Daniel; Kinuthia, John; Richardson, Barbra A.; Horne, David J.; John-Stewart, Grace
Abstract : Background: Peripartum immunologic changes may affect latent tuberculosis infection (LTBI) diagnostic performance among HIV-infected women. Methods: HIV-infected women were serially tested with tuberculin skin test (TST) and interferon gamma release assay [QuantiFERON TB Gold In-tube (QFT)] in pregnancy and 6 weeks postpartum in Kenya. Prevalence, sensitivity and agreement, and correlates of QFT/TST positivity were assessed. Quantitative QFT mitogen and Mycobacterium tuberculosis antigen (Mtb-Ag) responses were compared by peripartum stage. Incidence of test conversion at 6 weeks postpartum was evaluated in baseline TST−/QFT− women. Results: Among 100 HIV-infected women, median age was 26 years, median CD4 was 555 cells per cubic millimeter, and 88% were on antiretrovirals. More women were QFT+ than TST+ in both pregnancy (35.4% vs. 13.5%, P = 0.001) and postpartum (29.6% vs. 14.8%, P < 0.001). Among 18 consistently QFT+ women, 8 (44%) converted from TST− to TST+, with improved test agreement postpartum (56.9%, κ = 0.20 to 82.4%, κ = 0.60). Three initially QFT−/TST− women had test conversion (TST+ and/or QFT+), suggesting new infection (incidence 13.4/100 person-years). Mean QFT mitogen (4.46 vs. 7.64 IU/mL, P < 0.001) and Mtb-Ag (1.03 vs. 1.54 IU/mL, P = 0.03) responses were lower among all women retested in pregnancy vs. postpartum, and specifically among persistently QFT+ women (Mtb-Ag: 3.46 vs. 4.48 IU/mL, P = 0.007). QFT indeterminate rate was higher in pregnancy (16%) compared with postpartum (0%) because of lower mitogen response. Conclusions: QFT identified >2-fold more women with LTBI compared with TST in pregnancy and postpartum. Lower QFT Mtb-Ag and mitogen responses in pregnancy compared with postpartum suggest that pregnancy-associated immunologic changes may influence LTBI test performance. Abstract : Supplemental Digital Content is Available in the Text.